PENINGKATAN BERPIKIR MATEMATIS MELALUI IMPLEMENTASI MODEL PROBLEM BASED LEARNING SISWA SD - Pasaribu, Rosida Minta Ito; Surya, Edy; Fauzi, Muhammad Amin (Jurnal Merah Putih Sekolah Dasar, 2024)
The study's overarching goal is to determine, based on students' initial mathematics abilities, whether problem-based learning or more traditional methods of teaching mathematics improves students' critical and creative thinking skills in the subject. The 2013 curriculum includes problem-solving as an ability, therefore it's clear that this is an area that needs a lot of work. Among the many approaches to learning that adhere to Polya's stages is the Problem Based Learning (PBL) paradigm. Using a descriptive approach, this study included four sessions of instruction, one assessment of learning outcomes, and a study of remediation and enrichment. Learning outcomes examinations, expert validation of lesson plans and student activities, and observation of students' problem-solving abilities were all part of the data gathering process. The findings indicated that, according to the criteria, problem-based learning (PBL) is an effective model for teaching mathematics, and that students' abilities to solve problems using Polya's steps with PBL are also good.